A Closer Look at EFL Learners’ Problems and Strategies Used in Online Learning - Andini Nailatus Sarifah; Ahmad Ridho Rojabi; Moch. Imam Machfudi (Universitas PGRI Adi Buana Surabaya, 2024)
The transition from offline to online mode causes problems in education, especially in vocational high schools. These problems appear since learners are still adapting to the most recent instructional mode; online learning. This study aimed to look at problems of internal as well as external faced by EFL learners in online learning and the strategies to overcome those problems. This qualitative study with phenomenology was carried out. Ten participants from junior high school students were recruited by using a purposive sampling technique. The result showed that intelligence, interest, and motivation become their internal problems. While technology and pedagogical e-learning become external factors. The strategies used by the students were consulting dictionaries for meaning and pronunciation, navigating the course contents, discussing with peers and family, reviewing course materials, engaging in some hobbies, utilizing additional applications, and setting up timetables to study. The present study offers significant contributions to the advancement of online instruction as a whole by providing insightful information.